The risks of overlooking the diagnosis of secreting pituitary adenomas. Issue 1 (December 2016) - Brue, Thierry; Castinetti, Frederic
Abstract Secreting pituitary adenomas that cause acromegaly and Cushing's disease, as well as prolactinomas and thyrotroph adenomas, are uncommon, usually benign, slow-growing tumours. The rarity of these conditions means that their diagnosis is not familiar to most non-specialist physicians. Consequently, pituitary adenomas may be overlooked and remain untreated, and affected individuals may develop serious comorbidities that reduce their quality of life and life expectancy. Because many signs and symptoms of pituitary adenomas overlap with those of other, more common disorders, general practitioners and non-endocrinology specialists need to be aware of the "red flags" suggestive of these conditions. A long duration of active disease in patients with secreting pituitary adenomas is associated with an increased risk of comorbidities and reduced quality of life. Appropriate treatment can lead to disease remission, and, although some symptoms may persist in some patients, treatment usually reduces the incidence and severity of comorbidities and improves quality of life. Therefore, correct, early diagnosis and characterization of a pituitary adenoma is crucial for patients, to trigger timely, appropriate treatment and to optimize outcome. This article provides an overview of the epidemiology of hormonal syndromes associated with pituitary adenomas, discusses the difficulties of and considerations for their diagnosis, and reviews the comorbidities that may develop, but can be prevented, by accurate diagnosis and appropriate treatment. We hope this review will help general practitioners and non-endocrinology specialists to suspect secreting pituitary adenomas and refer patients to an endocrinologist for confirmation of the diagnosis and treatment.